2014
DOI: 10.2147/dhps.s66496
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bactericidal activity of Hannon honey on slowly growing bacteria in the chemostat

Abstract: There is renewed interest in the therapeutic use of honey, including use in the treatment of infected wounds and burn patients. In this study, we have assessed the antibacterial activity of Libyan floral Hannon honey on Escherichia coli and Staphylococcus aureus, both known to infect wounds. The effects of four concentrations (5%–30%) of honey were compared with that of four antibiotics (ampicillin, tetracycline, polymyxin, and ciprofloxacin) on the growth of these bacteria at early log, mid log, and late log … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Acidity of honey (pH range from 3.2 to 4.5) or activity of glucose oxidase in the ripening of nectar [ 43 ]. The presence of hydrogen peroxide [ 44 , 45 ], endogenous hydrogen peroxide content [ 11 , 22 ], inhibin [ 23 ] which acts as antibacterial factor other than H 2 O 2 [ 24 ], hydrogen peroxide [ 25 ], non-peroxide substances [ 46 , 47 ], defensin-1, as well as the presence of phytochemical factors [ 27 , 28 ] and phytochemical components [ 17 , 24 , 29 , 30 ]. The antibacterial activity of different honey was studied by several authors [ 5 - 8 , 20 , 21 , 33 - 36 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acidity of honey (pH range from 3.2 to 4.5) or activity of glucose oxidase in the ripening of nectar [ 43 ]. The presence of hydrogen peroxide [ 44 , 45 ], endogenous hydrogen peroxide content [ 11 , 22 ], inhibin [ 23 ] which acts as antibacterial factor other than H 2 O 2 [ 24 ], hydrogen peroxide [ 25 ], non-peroxide substances [ 46 , 47 ], defensin-1, as well as the presence of phytochemical factors [ 27 , 28 ] and phytochemical components [ 17 , 24 , 29 , 30 ]. The antibacterial activity of different honey was studied by several authors [ 5 - 8 , 20 , 21 , 33 - 36 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we could have concluded that the variations in the activity of different honey were attributed to the previously mentioned factors which influenced the antibacterial activity [ 7 ] as osmotic properties of honey [ 20 , 39 ]; honey pH or activity of glucose oxidase [ 41 ]; hydrogen peroxide [ 42 , 45 ], non-peroxide substances [ 46 , 47 ], presence of propolis which contain flavonoid [ 46 ], and volatile antibacterial substances [ 40 ].…”
Section: Discussionmentioning
confidence: 99%